Driving value with spring goals : humble plans, exceptional results - Dalmijn, Maarten (Addison-Wesley signature series., 2024)
Building great software requires outstanding teamwork across multiple disciplines. All teams and participants need to align behind clear goals that deliver real value (outcomes), not just lots of features (output). Sprint Goals are the most powerful tool Scrum/Agile teams have to pursue high-value outcomes, but many Scrum Teams avoid them, misuse them, or struggle to apply them. Succeeding with Sprint Goals covers everything you need to define, create, and execute on Sprint Goals that deliver outstanding value to customers and the business. Leading Scrum practitioner Maarten Dalmijn bridges the gap between theory and practice, offering a fresh, unique, and cohesive perspective on the Scrum framework that will be valuable to every Product Owner, Product Manager, Scrum Master, Agile coach, and technology executive. You will learn why Sprint Goals are so important, how to use them throughout the Sprint and at Review and Retrospective, how to overcome common obstacles to success, and how to use them to build high-performing teams. As Dalmijn presents critical Scrum and product management fundamentals through the lens of the Sprint Goal, he helps you move your entire organization from low-value "feature factories" to high-value outcomes.